Permethrin-induced morphological changes in oocytes of Rhipicephalus sanguineus (Acari: Ixodidae) semi-engorged females - Roma, Gislaine Cristina [UNESP]; Scopinho Furqium, Karim Christina [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
The permethrin, active ingredient of the Advantage (R) Max3 - Bayer, has been widely used in the chemical control of ticks. These ectoparasites are one of the most important animal groups that cause serious damage to their hosts. This study evaluated the toxic effects of permethrin in oocytes of Rhipicephalus sanguineus; semi-engorged females subjected to four treatments: group I (control - distilled water), group II (206 ppm of permethrin), group III (1031 ppm of permethrin) and group IV (2062 ppm of permethrin). Results demonstrated that permethrin is a potent chemical agent causing major structural changes in oocytes, such as emergence of large vacuolated cytoplasm regions, reducing the amount of yolk granules and decreasing the size of oocytes, culminating with cell death. As reported in the literature, these oocytes changes, besides affect the tick nervous system, also drastically reduce or prevent the reproduction process in females of R. sanguineus ticks subjected to this compound. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Rhipicephalus sanguineus; Permethrin; Acaricide; Oocytes; Cytotoxicity; Reproduction